2021
DOI: 10.1021/acs.inorgchem.1c00890
|View full text |Cite
|
Sign up to set email alerts
|

Tricarboxylic-Ligand-Decorated Lanthanoid-Inserted Heteropolyoxometalates Built by Mixed-Heteroatom-Directing Polyoxotungstate Units: Syntheses, Structures, and Electrochemical Sensing for 17β-Estradiol

Abstract: Organic−inorganic hybrid metal−oxide clusters have been pursued for many years, benefiting from their abundant structures and prominent performances. Upon our exploration, a family of unusual mixed-heteroatom (Sb III , P III )-directing lanthanoid (Ln)-inserted h eteropolyoxotungstates ( Ln-HPOTs),functionalized by 1,2,3-propanetricarboxylic acid (H 3 ptca) was a c h i e v e d . T h e i n t r i g u i n g t r i m e r i c [ L n 4 ( H12− polyanion was established by two trivacant [B-α-Sb III W 9 O 33 ] 9− segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…The process for the fabrication of the nano-1/NH 2 -G composite is schematically represented in Scheme 1a-c. As is known, the introduction of an active substrate possessing a high-specific surface area and electroconductibility is a useful method to promote the electrochemical application of POM-based materials. 31,32 NH 2 -G is an ideal conductive substrate due to its low cost, high electrical conductivity, amino-functionalized surface and huge surface area. Also, NH 2 -G possesses abundant active sites to combine with POMs based on supramolecular interactions and electrostatic attraction.…”
Section: Design Strategy and Characterization Of Nano-1 And Nano-1/ N...mentioning
confidence: 99%
“…The process for the fabrication of the nano-1/NH 2 -G composite is schematically represented in Scheme 1a-c. As is known, the introduction of an active substrate possessing a high-specific surface area and electroconductibility is a useful method to promote the electrochemical application of POM-based materials. 31,32 NH 2 -G is an ideal conductive substrate due to its low cost, high electrical conductivity, amino-functionalized surface and huge surface area. Also, NH 2 -G possesses abundant active sites to combine with POMs based on supramolecular interactions and electrostatic attraction.…”
Section: Design Strategy and Characterization Of Nano-1 And Nano-1/ N...mentioning
confidence: 99%
“…Moreover, compared with pure inorganic HPOMs, OIHHPOMs possibly possess unpredictable properties due to synergetic effects of inorganic HPOMs and organic ligands. It can be explicitly found that organic rigid ligands especially those who own benzene ring or N-heterocycle in their structures are more frequently selected to build OIHHPOMs because strong coordination ability and settled coordination sites are available to construct extended structures (Figure f–j). On the contrary, coordination modes of flexible organic ligands are much fickle due to freely rotating C–C bonds in carbochains, which also can be as commendable factors to form preeminent structures. Most of flexible organic ligands introduced in OIHHPOMs are short-chain ligands such as amino acid, ethylenediamine, and so on (Figure k–o). However, seeking applicable organic ligands to synthesize innovative OIHHPOMs still face huge challenges that need constant endeavor of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, because of the too small steric hindrance of the hydrogen atom on it, the tetrahedral coordination behavior of the [HPO 3 ] 2– anion is usually like the triangular pyramidal coordination configuration of the [TeO 3 ] 2– anion. This stereochemical feature of the [HPO 3 ] 2– ion tends to integrate with tungsten centers and creates novel open-framework phospho­(III)­tungstate fragments. (2) Although the triangular pyramidal [TeO 3 ] 2– and tetrahedral [HPO 3 ] 2– groups in the coexisting reaction system might be competitive, the stereochemical active difference of [TeO 3 ] 2– and [HPO 3 ] 2– groups will be very likely to produce negatively charged and defect P III -templating and Te IV -templating mixed HPOT BBs, which can strongly capture positively charged RE cations for constructing uncommon PTHSTREHs and will greatly enrich the structural types of POMs. (3) The addition of cerium acetate provides not only Ce 3+ ions but also acetate as the ligand.…”
Section: Introductionmentioning
confidence: 99%